2022
DOI: 10.1038/s41514-022-00096-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential blood biomarkers for early diagnosis of Alzheimer’s disease through immune landscape analysis

Abstract: Mild cognitive impairment (MCI) is a clinical precursor of Alzheimer’s disease (AD). Recent genetic studies have reported on associations between AD risk genes and immunity. Here, we obtained samples and data from 317 AD, 432 MCI, and 107 cognitively normal (CN) subjects and investigated immune-cell type composition and immune clonal diversity of T-cell receptor (TRA, TRB, TRG, and TRD) and B-cell receptor (IGH, IGK, and IGL) repertoires through bulk RNA sequencing. We found the proportions of plasma cells, γδ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Xu et al previously reported that the diversity of TCR repertoires was significantly lower in samples from AD patients than in samples from CN individuals, as analyzed with single-cell RNA-seq 34 . Our previous study also reported that the diversity of B-cell receptor repertoires (IGH and IGK) and TRA were significantly smaller in people with LOAD progression, using a large number of RNA-seq datasets (> 850 Japanese samples) 35 . These results suggest that the DRB1*09:01-DQB1*03:03 haplotype and the diversity of TCR repertoires could potentially be associated with the onset of LOAD through different mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…Xu et al previously reported that the diversity of TCR repertoires was significantly lower in samples from AD patients than in samples from CN individuals, as analyzed with single-cell RNA-seq 34 . Our previous study also reported that the diversity of B-cell receptor repertoires (IGH and IGK) and TRA were significantly smaller in people with LOAD progression, using a large number of RNA-seq datasets (> 850 Japanese samples) 35 . These results suggest that the DRB1*09:01-DQB1*03:03 haplotype and the diversity of TCR repertoires could potentially be associated with the onset of LOAD through different mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…Briefly, 2 μg of the Aβ42 peptide was coated to the surface of the immunotube with a high binding surface (SPL Life Sciences, 43015) for 16 hours at 4°C, and blocked with 5 ml of 3% bovine serum albumin (BSA) in PBS (w/v). Then the scFv phage library (about 10 13 phages) was incubated for 2 hours at room temperature. During the first round of panning, the tube was washed once with 5 ml of 0.05% (v/v) Tween 20 (Sigma-Aldrich, P1379) in phosphate-buffered saline (PBST).…”
Section: Methodsmentioning
confidence: 99%
“…B cells play a fundamental role in the adaptive immune system particularly in humoral immunity, by recognizing antigens via membrane-expressed B cell receptors (BCR) and producing antigen-specific immunoglobulin (Ig) in response 12 . Accordingly, recent studies have investigated the differences in immune cell type compositions and the clonal diversity of BCR repertoires among AD patients through single-cell RNA sequencing data or single-cell BCR libraries of peripheral blood mononuclear cells (PBMCs) 5,13 . The results showed that the proportion of B cells and the clonal diversity of both the heavy and kappa () light chains of BCR repertoires all significantly decreased with the progression of AD.…”
Section: Introductionmentioning
confidence: 99%